Investigation of Personality Traits between Infertile Women Submitted to Assisted Reproductive Technology or Surrogacy - Asgari, Najmeh (Int J Fertil Steril, 2016)
BACKGROUND: Personality traits affect human relationships, social interactions, treatment procedures, and essentially all human activities. The purpose of this study is to investigate the personality traitsincluding sensation seeking, flexibility, and happiness among a variety of infertile women who were apt to choose assisted reproductive technology (ART) or surrogacy. MATERIALS AND METHODS: This is a cross-sectional study that was performed on 251 infertile women who visited Isfahan and Tehran Reproductive Medicine Center. These fertility clinics are located in Isfahan and Tehran, Iran. In this study, 201 infertile women who underwent treatment using ART and 50 infertile women who tended to have surrogacy were chosen by convenience sampling. Zuckerman’s Sensation Seeking Scale Form V (SSS-V), Psychological Flexibility Questionnaire (adapted from NEO Personality Inventory-Revised) and Oxford Happiness Questionnaire (OHQ) were used as research instruments. All participants had to complete the research instruments in order to be included in this study. Data were analyzed by descriptive-analytical statistics and statistical tests including multivariate analysis of variance (MANOVA) and Z Fisher. Statistically significant effects were accepted for P<0.05. RESULTS: In the sensation-seeking variable, there was a meaningful difference between under-study groups. However, the flexibility and happiness variables did not have a significant difference between under-study groups (P<0.001). Interaction between education, employment, and financial status was effective in happiness of infertile women underwent ART (P<0.05), while age, education and financial status were also effective in happiness of infertile women sought surrogacy (P<0.05). A positive meaningful relationship was seen between sensation seeking and flexibility variables in both groups (P<0.05). And a negative meaningful relationship was seen between sensation seeking and happiness in infertile women who sought surrogacy (P<0.05). The difference in rate of relationship between sensation seeking and flexibility was meaningful in infertile women who sought either ART or surrogacy (P<0.05). CONCLUSION: Sensations seeking as a personality trait is lower in infertile women who underwent treatment using ART compared women who tended to have surrogacy. This study shows that demographic variables are effective in happiness of infertile women. Also, there is a significant relation among sensation seeking, flexibility and happiness in infertile women.